The effects of different epidural analgesia formulas on labor and mode of delivery in nulliparous women - Shin-Yan Chen; Pei-Lin Lin; Yu-Hsuan Yang; Ya-Min Yang; Chien-Nan Lee; Shou-Zen Fan; Li-Kuei Chen (Elsevier, 2014)
Objectives: Patient-controlled epidural analgesia (PCEA) and continuous epidural infusion (CEI) are popular and effective methods for pain relief during labor; however, there are concerns about increasing rates of cesarean section (C/S) and instrumental delivery. This prospective study investigated the effect of PCEA and CEI with different formulas on labor and the mode of delivery in nulliparous women. Materials and methods: A total of 480 nulliparous women were randomized into four groups, with 120 in each. Group A received a loading dose of 10 mL of 1 mg/mL ropivacaine with 2 μg/mL fentanyl, then an intermittent bolus of 5 mL with a background infusion of 5 mL/hour by PCEA. Group B received the same PCEA formula as Group A with 0.8 mg/mL bupivacaine. Group C received the same formula as Group A by CEI with 1 mg/mL ropivacaine at a rate of 10 mL/hour. Group D received the same formula as Group C with 0.8 mg/mL bupivacaine. The rates of C/S and instrumental delivery and the incidence of side effects were recorded. Results: The rates of C/S were significantly different between Groups A and C, Groups A and D, and Groups B and D. The rates of instrumental delivery for normal spontaneous delivery were significantly different between Groups A and B, A and D, B and C, and C and D. Conclusion: The C/S rate was higher in Groups C and D; however, the instrumental delivery rate was lower in Groups A and C. We conclude that PCEA with 1 mg/mL ropivacaine might provide the greatest benefit for labor analgesia.